Economic optimization of coastal flood defense systems. (March 2017) - Dupuits, E.J.C.; Schweckendiek, T.; Kok, M.
Abstract: Coastal flood defense systems can consist of multiple lines of defense. In case of a system with a front and a rear defense (e.g. a storm surge barrier and levees), the front defense can improve the reliability of the rear defense by reducing the load on this rear defense. This paper develops a framework in order to assess whether including the influence of such a load reduction influences the economically optimal safety targets of both defenses. The economic optimization is carried out using two approaches: a simplified method developed to explore the behavior of the economic optimization with a front and rear defense, and a numerical framework geared towards practical applications. The numerical framework provides more flexibility in defining risk, cost and damage functions, and emphasizes on the applicability and tractability of the necessary steps from an engineering perspective. Both approaches are used in a hypothetical case study in order to quantify the effect of including a load reduction on the economically optimal safety targets. The results indicate that if a front defense can create a significant risk reduction in a cost efficient manner, more efficient economically optimal safety targets can be found by including the load reduction. Abstract : Highlights: In a coastal system, a front defense improves the reliability of the rear defense. This interaction is analytically incorporated in a simplified economic optimization. For more complex (realistic) economic optimization, a numerical framework is proposed. Including the interaction of a coastal system improves flood prevention investments.